Paracentral acute middle maculopathy as a finding in patients with severe vision loss following phacoemulsification cataract surgery. (25th April 2017) - Creese, Katarina; Ong, Daini; Sandhu, Sukhpal S; Ware, David; Alex Harper, C; Al‐Qureshi, Salmaan H; Wickremasinghe, Sanjeewa S
Abstract: Importance: Paracentral acute middle maculopathy (PAMM) diagnosed by spectral domain optical coherence tomography (SD‐OCT) in patients with poor visual outcome post cataract surgery. Background: Case series of severe vision loss due to PAMM after cataract surgery. Design: Retrospective case series. Participants: Cases from five surgical centres in Victoria, Australia. Methods: Retrospective analysis of cases with unexplained 'patch‐off' vision loss post cataract surgery. All patients in our cohort had PAMM and presumed diagnosis of central or transient retinal artery occlusion. Main Outcome Measures: A review of the patient histories focusing on pre‐operative ocular and systemic vascular risk factors, anaesthetic and operative factors. Results: Ten cases were included. All patients had 6/72 Snellen visual acuity or worse noted on day one post surgery. Three patients had features of central retinal artery occlusion consisting of retinal pallor with a 'cherry red' macula but absent relative afferent pupillary defect. Seven had no features of retinal pallor or attenuation of retinal arterioles. On SD‐OCT, all eyes had evident PAMM. Six patients had a history of cardiovascular disease or blood dyscrasia. Conclusions and Relevance: PAMM should be considered in patients with 'patch off' visual loss and absence of other fundal signs. We hypothesise that spasm or transient occlusion of central retinal artery leads to arterial hypoperfusion with subsequent ischaemia or infarction of the retina. Underlying arterial disease may have led to pre‐existing hypoperfusion that may have been further compromised by raised intraocular pressure during the procedure itself or via raised orbital pressure from the anaesthesia.